The possible takeover of Commerzbank by UniCredit - Carl Heinz Daube (ZBW - Leibniz Information Centre for Economics, 2024)
This article analyses the potential impact of a takeover of Commerzbank by the Italian bank UniCredit on the European banking landscape and the development of the Capital Markets Union. It discusses the potential for increased profitability, structural efficiency and stability of the European banking sector as well as the challenges associated with the consolidation of banks. Finally, it examines how this takeover could contribute to achieving the objectives of the Capital Markets Union by improving the framework conditions for financing, particularly for SMEs. – – Dieser Artikel analysiert die möglichen Auswirkungen einer Übernahme der Commerzbank durch die italienische Bank UniCredit auf die europäische Bankenlandschaft und die Entwicklung der Kapitalmarktunion. Er erörtert das Potenzial für eine höhere Rentabilität, strukturelle Effizienz und Stabilität des europäischen Bankensektors sowie die mit der Konsolidierung von Banken verbundenen Herausforderungen. Schließlich wird untersucht, wie diese Übernahme zur Erreichung der Ziele der Kapitalmarktunion beitragen könnte, indem sie die Rahmenbedingungen für die Finanzierung, insbesondere von KMU, verbessert.
Keywords: G01; 330; UniCredit; Commerzbank; EU Capital Market Union; Next CMU